(untitled) (Research, Society and Development, 2020)
Some animal species exhibit reproductive seasonality regulated mainly by the daily photoperiod, may be modulated by climate and food. This physiological characteristic is well known and prominent in females, where happens a period of breeding season and other anestrus. However, in males of species seasonal the reproductive variations are not considered sufficient to prevent reproduction throughout the year, but must consider such changes in some husbandry practices and decision making. The aim of this review is to evaluate the influence of photoperiod on reproduction of male goats and sheep, and also, possible actions of melatonin on sperm conservation directly and indirectly.